Size Effect of Fe3O4 Nanoparticles on Magnetism and Dispersion Stability of Magnetic Nanofluid - Chen, Fang; Ilyas, Nasir; Liu, Xiaobing; Li, Zhenggui; Yan, Shengnan; Fu, Hao (Frontiers in Energy Research, 2021)
It is well known that magnetic nanofluids are widely applied in various fields ranging from heat transfer to miniature cooling, and from damping to sealing, due to the mobility and magnetism under magnetic field. Herein, the PFPE-oil based magnetic nanofluids with superior magnetization and dispersion stability were obtained via regulating reaction temperature. The structures of particles were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The size effects of particles on the magnetism and coating effect of particles, and on the stability and saturation magnetization of the fluids were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), vibrating sample magnetometer (VSM) and density instrument, respectively. The results indicate that the impurity phase FeOOH only appear in the sample prepared at 18°C and the average size of Fe3O4 nanoparticles reduces from 120 to 20 nm with raising reaction temperature. The saturation magnetization of Fe3O4 particles increases firstly and then reduces with increasing particle size, which is affected by the thickness of magnetic dead layer and impurity phase FeOOH. The Fe3O4 particles could be chemically coated by PFPE-acids, and the coated mass is a little affected by particle size. The stability of the nanofluids lowers while the saturation magnetization increases firstly and then decrease with increasing particle size. At reaction temperature of 60°C, Fe3O4 particles of 25 nm and the nanofluids with superior stability and saturation magnetization were obtained. Our results indicate that the control of nanoparticles size by regulating reaction temperature can be a useful strategy for preparing magnetic nanofluids with desirable properties for various potential applications.